A study of the workers’ working conditions in areas of the manufacture castings from copper alloys - A. M. Lazarenkov; I. A. Ivanov; M. A. Sadokha (Литьë и металлургия)
The results of the study of workers working conditions at the areas of the manufacture of castings from copper alloys are presented. It is noted that the main production factors of working conditions are noise, vibration, dustiness, gas contamination, temperature, intensity of infrared (thermal) radiation, severity and labor process intensity. The results have shown that at all workplaces there are exceedances of permissible values for noise and local vibration, the content of dust and harmful substances in the air of the working environment, the intensity of infrared (thermal) radiation and temperature. It is noted that the work performed due to the severity and labor process intensity can negatively affect the workers’ health.